2006
DOI: 10.1128/aac.50.1.88-95.2006
|View full text |Cite
|
Sign up to set email alerts
|

Resistance ofLeishmania donovanito Sodium Stibogluconate Is Related to the Expression of Host and Parasite γ-Glutamylcysteine Synthetase

Abstract: Sequencing studies showed that the ␥-glutamylcysteine synthetase (␥-GCS) heavy chain genes from sodium stibogluconate (SSG)-resistant (SSG-R) and SSG-susceptible (SSG-S) Leishmania donovani strains were identical, indicating that SSG resistance was related to quantitative differences in ␥-GCS expression rather than gene interstrain polymorphisms. In vitro infection of murine macrophages with the SSG-R strain, but not the SSG-S strain, down regulated expression of host ␥-GCS, which would result in a reduction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 38 publications
1
40
0
2
Order By: Relevance
“…Therefore, the in vivo chemotherapeutic outcome of antimonial therapy depends on the susceptibility of the parasite not only to the antimonial compound but also to other host-derived microbicidal molecules. Likewise, during treatment, the outcome of pentavalent antimonial therapy in vivo correlates with tolerance towards macrophage-derived microbicidal factors (Carter et al 2005;Carter et al 2006). The acquisition of drug resistance by Leishmania markedly alters the response of the host immune system following parasitic infection (Haldar et al 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, the in vivo chemotherapeutic outcome of antimonial therapy depends on the susceptibility of the parasite not only to the antimonial compound but also to other host-derived microbicidal molecules. Likewise, during treatment, the outcome of pentavalent antimonial therapy in vivo correlates with tolerance towards macrophage-derived microbicidal factors (Carter et al 2005;Carter et al 2006). The acquisition of drug resistance by Leishmania markedly alters the response of the host immune system following parasitic infection (Haldar et al 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Our group and others have shown that the interaction between Leishmania and the human host extends beyond modulation of immunological functions to determinants of pharmacological responses [19-24]. L. (V.) panamensis infection of primary human macrophages and exposure to meglumine antimoniate (MA) or miltefosine modulate the expression of host cell ABC transporters and Solute Liquid Carriers (SLC), metabolic enzymes and scavenging molecules, differentially regulating the antileishmanial effect of these drugs [19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…L. (V.) panamensis infection of primary human macrophages and exposure to meglumine antimoniate (MA) or miltefosine modulate the expression of host cell ABC transporters and Solute Liquid Carriers (SLC), metabolic enzymes and scavenging molecules, differentially regulating the antileishmanial effect of these drugs [19, 20]. Sb-resistant L donovani strains have been shown to induce expression of macrophage ABC transporters P-glycoprotein (P-gp), Multidrug resistance associated protein–1 (MRP-1) [21] and repression of macrophage gamma-glutamylcysteine synthetase (γ-GCS) [24], resulting respectively in reduced antimony accumulation and limited reduction to SbI II in cells infected with Sb-resistant parasites. These findings lend support to the concept that drug resistance in Leishmania can be conferred by a multiplicity of redundant mechanisms dependent both on the parasite and the host.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that an increase in GCLM expression could lead to an increase of GSH (8). Indeed, GSH reduces SbV to SbIII nonenzymatically (37), and the activity of SbV was associated with the manipulation of both host and parasite GSH levels by the parasite (6). Thiol levels are known to be important for the parasite itself, where SbIII decreases the level of intracellular GSH (21,43), and an increased level of thiols is associated with resistance to antimonials (15,22,24).…”
Section: Vol 52 2008 Gene Expression Changes Mediated By Pentostam 531mentioning
confidence: 99%